evaluate the question

This question is asking you to put the number **3** wherever you see an **x**.

So, if we do that, we'll then have the equation f(**3**) = **3** + 4, which simplifies to f(**3**) =
**7**.

Send me a comment if you need any more help!

evaluate the question

Tutors, please sign in to answer this question.

This question is asking you to put the number **3** wherever you see an **x**.

So, if we do that, we'll then have the equation f(**3**) = **3** + 4, which simplifies to f(**3**) =
**7**.

Send me a comment if you need any more help!

Simply replace f(x) with 3, which now gives you f(x)= 3 + 4. Add those numbers together, and f(3) gives you 7.

f(x) = x + 4

f(3) = (3) + 4

f(3) =7

f(x)=x+4

we need f(3)

so we just replace the value of x to 3 and replace in the original function of x or f(x)=x+4

f(3)=3+4

=7 thats your answer

x = 3

so 3 = 3 + 4

and 3 + 4 = 7

so the answer is 3 = 7

Let's start with some basic information.

**f(x) means the function of x**, just like with a slope equation or a y equation. If it makes it easier, you can think of f(x) to be the same as y.
**All it does is explain the relationship between f(x) or y to variable x.**

So if f(x) = x+4, that means that for any value (x), f(x) is equal to x+4.

Now, the question asks, what if x was equal to 3?

This changes the original **f(x)= x+4**

to **f(3)= 3+4**

Then you just do the addition: 3+4= 7

Therefore: **f(3)= 3+4, f(3)= 7**

Nafeesa M.

Expert SAT, ACT, Math, and French Tutor!

New York, NY

4.9
(115 ratings)

Thomas D.

Aerospace Engineer tutoring in Math/Science

Great Neck, NY

5.0
(61 ratings)

Romina A.

Knowledgeable tutor in Spanish, Biology, Anatomy & Physiology and Math

Harrison, NJ

5.0
(166 ratings)